VD_FINDINFO Décision / 2013 / 913 vom 4. November 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, PROLONGATION, RISQUE DE FUITE, RISQUE DE RÉCIDIVE | 221 CPP (CH), 222 CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)